8x-3(x-1)=4x+2

Simple and best practice solution for 8x-3(x-1)=4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3(x-1)=4x+2 equation:


Simplifying
8x + -3(x + -1) = 4x + 2

Reorder the terms:
8x + -3(-1 + x) = 4x + 2
8x + (-1 * -3 + x * -3) = 4x + 2
8x + (3 + -3x) = 4x + 2

Reorder the terms:
3 + 8x + -3x = 4x + 2

Combine like terms: 8x + -3x = 5x
3 + 5x = 4x + 2

Reorder the terms:
3 + 5x = 2 + 4x

Solving
3 + 5x = 2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 5x + -4x = 2 + 4x + -4x

Combine like terms: 5x + -4x = 1x
3 + 1x = 2 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + 1x = 2 + 0
3 + 1x = 2

Add '-3' to each side of the equation.
3 + -3 + 1x = 2 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 2 + -3
1x = 2 + -3

Combine like terms: 2 + -3 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| 7y+35x=490 | | y=5(8)+7 | | 4x-2+2x=14 | | 2v/5=30 | | (4x-2)+(5x+1)=2x+14 | | 1/4c7= | | y=4(y-13)-2 | | 7x+9=15+x | | 3(2n-10)=17 | | (2x/3y)^5 | | x/12=24/24-x | | 1(84+14y)-7y=-7 | | a/3=5=11 | | 6(4+4x)=240 | | (4x+3)+7x*(4x+3)=16x-1 | | 10x=-10+40 | | -6(5+4n)=-78 | | 1+5x=7x-21 | | (4x-18)+(7x+21)+(3x+51)=180 | | 9x^2=-12x+4 | | 51-3+5k=58 | | (4x+3)+(7x)=16x-1 | | x^6+9x^3+5x-8=0 | | (4x-18)+(7x+21)+(3y+51)=180 | | 6a+5a^2=48+(-10a)+5a^2 | | 1(-24-3y)+6y=18 | | (5x-48)+(6x+14)+(3x+46)=180 | | 3x-6y=8-4y | | X^2+288x-25088=0 | | 7+2x=5x-26 | | xmeio+17=30 | | 4(-3V-2)=56 |

Equations solver categories